The Effect of Charge Mass and Delay Timing on Airblast Overpressure - Alan Richards; Adrian Moore; Dominic Hooton (International Society of Explosives Engineers, 2025)
Significant factors affecting airblast overpressure (AOP) emissions include charge mass per delay, distance from the blast site, burden, stemming height, and delay timing, topographic shielding, and meteorology. The effect of charge mass on the frequency of the airblast produced, and the delay timing required to control the level of airblast overpressure is explained by two case history examples which were not affected by topographical shielding and meteorology. One is a cast blast with a charge mass per hole of 1000 kg (2200 lb), and the other is a quarry blast with a charge mass per hole of 64 kg (141 lb), These examples show that the delay interval necessary to prevent an increase in AOP levels must be increased with an increase in charge mass per hole. The effect of a ‘soft-start’ technique where a reduction in AOP levels is achieved by decking only the initial front-row holes is also illustrated.